Provider Perceptions of Barriers to HIV Care Among Women with HIV in Miami-Dade County, Florida, and Possible Solutions: A Qualitative Study - Melissa K. Ward PhD, MPH (SAGE Publishing, 2021)
In Miami-Dade County, women with HIV (WWH) enrolled in Ryan White Program (RWP) services belong to groups that have historically faced structural barriers to care. To examine provider perceptions of WWH's barriers to care and elicit possible solutions, we conducted semi-structured interviews (n = 20) with medical case managers and human immunodeficiency virus (HIV) healthcare providers from medical case management sites serving WWH enrolled in the Miami-Dade RWP. Verbatim transcripts were analyzed thematically by two coders through an iterative process; disagreements were resolved through consensus. Barriers included lack of disclosure and stigma, additional psychosocial barriers to care, structural and logistical barriers, and negative interactions with health care providers. Participant suggestions to address these barriers included strategies that support women and foster individualized services that are responsive to their lived experiences and needs. Other solutions, such as those related to transportation, housing, and general funding for the RWP, will require advocacy and policy change.